Exploring the factors affecting technology transfer in government-funded research institutes: The Korean case - Sehwan Ko; Woojoong Kim; Kangwon Lee (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Based on the resource dependence theory and the resource-based view, this study examined the impact of the resources and capabilities of government-funded research institutes (GRIs) on technology transfer. Panel analysis was performed on 21 GRIs in South Korea representing three mission types—basic future leading, public infrastructure, and industrialization—for the 2015–2019 period. The analysis confirmed that the factors affecting technology transfer performance differed among GRIs depending on their mission type. For basic future leading GRIs, the number of technology transfer cases was strongly associated with the number of research personnel, while there was a negative relationship between technology transfer and the total budget, the number of research publications, and the number of patent registrations. None of the variables affected the revenue from technology fees. Researchers at these GRIs appear to have a strong motivation for technology transfer, but the priority for resource allocation at the institutional level is the production of papers and patents rather than technology transfer. For public infrastructure GRIs, the number of patents held and the number of technology licensing office (TLO) personnel had a positive impact on the number of technology transfer cases, while none of the variables affected the revenue from technology fees. Thus, the number of patents is more favorable for technology transfer at this type of GRI compared to those that pursue a mission of basic future leading, possibly because their research focus is more related to engineering than to basic science. For industrialization GRIs, the number of TLO personnel affected the number of cases of technology transfer, and the number of patent registrations and TLO personnel affected the revenue from technology fees. The speed of technology development and industrial application is thus much faster in industrialization GRIs than in the other GRI types. The results of this analysis show that mission attributes are important drivers of technology transfer performance. This study thus offers policy implications by illustrating those different resources should be provided to different types of GRI to optimize their technology transfer performance.
Keywords: 650; technology transfer; government-funded research institutes; resource dependence theory; resource-based view; technology licensing office